An empirical study on the background of Trust in e-commerce: a new analysis of the Oliveira, Alhinho, Rita and Dhillon model (2017) (Management and Connections Journal, 2021)
With the growth of the Internet, much research has been done on the background of the intention to purchase in this medium. Based on a model proposed in 2003 and empirically validated in 2017, we used a survey to collect 220 responses and validated the model by modeling structural equations. As the main finding, the study identified the strong influence of Confidence in the declared purchase intention and also that the Reputation of a company has a greater (positive) influence on the dimensions of Confidence than Brand Recognition. Our results indicated more valid hypotheses than the original study, conducted in 2017, which supports the validity of the proposed theoretical model and the importance of replicating studies in scenarios other than the one originally proposed, with the objective of guaranteeing the external validity of the findings of scientific marketing research. Theoretical and managerial implications are presented
Keywords: trust; reputation; eletronic commerce